Unvaccinated Children Are an Important Link in the Transmission of SARS-CoV-2 Delta Variant (B1.617.2): Comparative Clinical Evidence From a Recent Community Surge - Li, Hongru; Lin, Haibin; Chen, Xiaoping; Li, Hang; Li, Hong; Lin, Sheng; Huang, Liping; Chen, Gongping; Zheng, Guilin; Wang, Shibiao; Hu, Xiaowei; Huang, Handong; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Objective: To evaluate the necessity of Covid-19 vaccination in children aged < 12 y by comparing the clinical characteristics in unvaccinated children aged < 12 y with vaccinated patients aged ≥ 12y during the Delta surge (B.1.617.2) in Putian, Fujian, China. Methods: A total of 226 patients with SARS-Cov-2 Delta variant (B.1.167.2; confirmed by Realtime PCR positive and sequencing) were enrolled from Sep 10th to Oct 20th, 2021, including 77 unvaccinated children (aged < 12y) and 149 people aged ≥ 12y, mostly vaccinated. The transmission route was explored and the clinical data of two groups were compared；the effect factors for the time of the nucleic acid negativization (NAN) were examined by R statistical analysis. Results: The Delta surge in Putian spread from children in schools to factories, mostly through family contact. Compared with those aged ≥ 12y, patients aged < 12y accounted for 34.07% of the total and showed milder fever, less cough and fatigue; they reported higher peripheral blood lymphocyte counts [1.84(1.32,2.71)×10^9/L vs. 1.31(0.94,1.85)×10^9/L; p<0.05), higher normal CRP rate (92.21% vs. 57.72%), lower IL-6 levels [5.28(3.31,8.13) vs. 9.10(4.37,15.14); p＜0.05]. Upon admission, their COVID19 antibodies (IgM and IgG) and IgG in convalescence were lower [0.13(0.00,0.09) vs. 0.12(0.03,0.41), p<0.05; 0.02(0.00,0.14) vs. 1.94(0.54,6.40), p ＜0.05; 5.46(2.41,9.26) vs. 73.63 (54.63,86.55), p＜0.05, respectively], but longer NAN time (18 days vs. 16 days, p=0.13). Conclusion: Children aged < 12y may be critical hidden spreaders, which indicates an urgent need of vaccination for this particular population.